(untitled) (World Bulletin of Management and Law, 2023)
The article analyzes the international legal aspects of the jurisdiction of the International Court of Justice. When analyzing this topic, attention is paid, first of all, to the study of jurisdiction in disputed cases and jurisdiction to issue advisory opinions, thereby studying the international experience of States and organizations on filing an application for recognition of the court’s jurisdiction as mandatory, attaching importance to the role of the international regulatory framework of this issue, for example, the Statute of the International Court of Justice. Also, the issues of the possibility of submitting an application and the specifics of submitting an application of the Republic of Uzbekistan were considered. In addition, the article presents the international experience of States from the history of the cases considered by the International Court of Justice, with what reservations, conditions and on the basis of which document they submitted applications. The main purpose of the article is to reveal the legal essence of the international legal aspects of the jurisdiction of the International Court of Justice, methods and methods of its recognition. Based on the research done, a legal conclusion was made on the scientific topic of the article